The translation of personal pronouns in French discourses into Indonesian - Sajarwa, Sajarwa (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Translation is the transfer of a message from a source-language text into an equivalent target-language text. Cultural differences between a source language and a target language always leave marks on a translation process. Language as part of culture influences the minds of its speakers, especially translators. French literary texts (as source texts) and their Indonesian translations (target texts) can provide examples of the differences between the reasoning process of French literary writers and that of Indonesian translators, particularly in the translation of pronouns with this topic being the focus of this present study. By carefully investigating how pronouns are translated in three French novels – Michael Tournier’s (1971) Vendredi ou la Vie Sauvage, Amin Maalout’s (1993) Le Rocher de Tanios, Gustave Flaubert’s (1972) Madame Bovary – this study’s analysis shows that the translation of French pronouns in literary texts into Indonesian results in various forms, namely pronouns, lexical equivalences, repetitions, and substitutions. The translation of the pronoun on, which signifies passive voice, results in equivalence in meaning despite the absence of formal correspondence, and thus conjures the Indonesian passive diatheses di- and ter-